PENGARUH IHSG SEBAGAI LEADING ECONOMIC INDICATOR DAN BUSINESS CONFIDENCE TERHADAP FOREIGN DIRECT INVESTMENT (Studi pada Negara Indonesia Periode 2004-2017) - Heni Triastuti; Suhadak Suhadak (Jurnal Administrasi Bisnis, 2019)
This research was conducted in view of the importance investor activity in analyzing the economic conditions in a country, one of which is through the Jakarta Composite Index (JCI) as a leading economic indicator and its relationship with business activities towards foreign direct investment. JCI as a leading economic indicator means that the JCI is able to be used as an economic indicator that precedes the economy as a whole or can be referred to as an indicator that is able to predict the economy. This research includes the type of explanatory research with a quantitative approach. Data are analyzed annually through the partial least square method that is carried out through the Smart PLS 3.2.8 application. Based on the data analysis test, it was found that results showed a significant positive effect between the JCI as a leading economic indicator and business confidence in Indonesia, while business confidence toward foreign direct investment did not find significant results, it means that the movement of business confidence did not affect foreign direct investment movements. Likewise JCI as a leading economic indicator has no influence on foreign direct investment. Kеywords: Jakarta Composite Index (JCI), Leading Economic Indicator, Business Confidence, Foreign Direct Investment АBSTRАK Penelitian ini dilakukan mengingat pentingnya kegiatan investor dalam menganalisa kondisi perekonomian suatu negara, salah satunya melalui Indeks Harga Saham Gabungan (IHSG) sebagai leading economic indicator dan hubungannya dengan aktivitas bisnis terhadap investasi asing langsung. IHSG sebagai leading economic indicator memiliki makna bahwa IHSG mampu digunakan sebagai indikator ekonomi yang bersifat mendahului perekonomian secara keseluruhan atau dapat disebut sebagai salah satu indikator yang mampu memprediksi perekonomian.  Penelitian ini termasuk jenis explanatory research dengan pendekatan kuantitatif. Data dianalisis secara tahunan melalui metode partial least square yang dilakukan melalui aplikasi Smart PLS 3.2.8. Berdasarkan uji analisis data ditemukan hasil yang menunjukkan adanya pengaruh signifikan posiif antara IHSG sebagai leading economic indicator terhadap business confidence di Indonesia, sedangkan business confidence terhadap foreign direct investment tidak ditemukan hasil yang signifikan artinya pergerakan business confidence tidak memiliki pengaruh terhadap pergerakan foreign direct investment, begitu juga IHSG sebagai leading economic indicator tidak memiliki pengaruh terhadap foreign direct investment. Kata Kunci: IHSG, Leading Economic Indicator, Business Confidence, Foreign Direct Investment